Antiretroviral therapy among patients with HIV in Almaty, Kazakhstan: the implication for HIV-associated tuberculosis control - Denebayeva, Alfiya; Abrahamyan, Arpine; Sargsyan, Aelita; Kentenyants, Karine; Zhandybayeva, Ainur; Nugmanova, Zhamilya; Nurkerimova, Anarkhan; Davtyan, Karapet; Tukeyev, Marat (The Journal of Infection in Developing Countries, 2020)
Introduction: Antiretroviral therapy (ART) is an effective preventive strategy against tuberculosis (TB) in people living with HIV (PLWH). In Kazakhstan, according to the revised HIV treatment guideline (2017), ART should be initiated immediately after HIV diagnosis established, regardless of CD4+ count. Aim: To evaluate the impact of early initiation of ART on TB infection in PLWH registered in the Center of Prevention and Control of AIDS, Almaty, Kazakhstan, between 2008 and 2018. Methodology: A retrospective cohort study was conducted using the data of 4,053 patients from electronic HIV case management system (2008-2018) (EHCMS). Results: The study revealed low rates (12.6%) of rapid ART (≤ 1 month after HIV diagnosis). Patients in the rapid ART initiation group were less likely to develop TB compared with those who started treatment >1 month after the HIV detection (odds ratio 1.6; 95% confidence interval [1.1, 2.2]; p = 0.00799). Interestingly, the risk for developing TB among patients receiving ART ≥ 1 month after HIV diagnosis was significantly higher compared with those not taking any treatment. The latter was explained by several confounding not addressed during the analysis, since ART was prescribed to patients with primarily deeper immunodeficiency, while the patients not receiving ART were less immunocompromised. Conclusion: Despite the recently changed HIV treatment guideline in Kazakhstan, ART is still initiated based on the disease severity. In 2018, the initiation of ART during the first month after HIV diagnosis increased by 50%. However, it is necessary to reduce the time to initiation of ART for all patients.